Prisms of Whiteness: A Critical Analysis of the Multicultural Competence of Pre-Service Teachers - Tolbert, Joshua B. L. (International Journal of Learning, Teaching and Educational Research, 2019)
This study endeavored to assess the cultural competency of pre-service teachers in a region of the United States with limited ethnic or linguistic diversity. To do this, the prior work of D’Andrea, Daniels, and Noonan (2003) was used to develop an updated survey instrument. Students at a small university in the Midwest were surveyed at multiple intervals during the course of their teacher education program, and their total responses (n=190) are analyzed here. Findings for reliability and validity of the instrument are discussed, as well as general trends when comparing students by course enrollment, major, and degree status. Further discussion centers on the potential discovery of a partial measure of white fragility and how the results of the study may be enhanced by applying a lens of critical whiteness. Finally, implications are presented regarding how white fragility might be directly and deliberately incorporated into future efforts to measure and develop cultural competency in pre-service teachers. https://doi.org/10.26803/ijlter.18.4.8